Prevention of Acetaminophen Induced Hepatorenal Toxicity in Mice with Fruits of Terminalia chebula (Myrobalan) - Sharma A; Rathore H.S. (Thai Journal of Toxicology, 2020)
Protective role of fruits of Terminalia chebula (myrobalan) at three dose levels (200,150 &100mg/kg bw) against acetaminophen (paracetamol) induced hepato and nephrotoxicity with single sublethal dose (300mg/kg bw) has been assessed. Parameters of study are glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT), billirubin, alkaline phosphatase (ALP) as liver function tests, creatinine and urea as kidney function tests and histology of liver and kidney for pathology. T.chebula could well antagonize acetaminophen induced hepatorenal toxicity in dose dependent manner. However, myrobalan could not afford protection against lethal dose of acetaminophen. Probable protective role is discussed in detail on the basis of known properties of different constituents of fruits of Terminalia chebula.